Relationship of Knowledge and Attitudes with Male Participation in Vasectomy in Indonesia (Medico Legal Update, 2021)
Family planning is an effort to control the birth of children, the ideal space and age for childbirth, pregnancycontrol, through promotion, protection, and assistance in accordance with reproductive rights to form aquality family. Vasectomy, or vas occlusion, is considered to be the most effective and very popular form ofcontraception. This study aims to analyze the relationship between knowledge and attitudes with vasectomyparticipation in men. This study used a cross-sectional approach. The research location is in Madiun City,East Java, Indonesia. The total sample in this study was 323 respondents. The variables in the study wereknowledge, attitudes, and participation in vasectomy family planning. There is a relationship betweenknowledge and attitudes about vasectomy with male participation in vasectomy.